2022
DOI: 10.3390/plants11212869
|View full text |Cite
|
Sign up to set email alerts
|

CsMYB Transcription Factors Participate in Jasmonic Acid Signal Transduction in Response to Cold Stress in Tea Plant (Camellia sinensis)

Abstract: Low-temperature stress is an increasing problem for the cultivation of tea (Camellia sinensis), with adverse effects on plant growth and development and subsequent negative impacts on the tea industry. Methyl jasmonate (MeJA), as a plant inducer, can improve the cold-stress tolerance in tea plants. R2R3-MYB transcription factors (TFs) are considered potentially important regulators in the resistance to cold stress in plants. However, the molecular mechanisms, by which MYB TFs via the jasmonic acid pathway resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 71 publications
0
10
0
Order By: Relevance
“…The relative expression of BrCMFs was significantly downregulated under short duration cold stress, and the expression of BrCMF15 of these genes was lowest under such conditions ( Figure 5 E, Table S3 ). Studies have shown that MeJA could promote reactive oxygen species (ROS) scavenging and contribute to the positive feedback regulation of melatonin (MT) to enhance the cold tolerance of plants [ 25 , 26 ], but BrCMF15 lacks MeJA-response elements. This is consistent with the high expression of the other genes according to the qPCR analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The relative expression of BrCMFs was significantly downregulated under short duration cold stress, and the expression of BrCMF15 of these genes was lowest under such conditions ( Figure 5 E, Table S3 ). Studies have shown that MeJA could promote reactive oxygen species (ROS) scavenging and contribute to the positive feedback regulation of melatonin (MT) to enhance the cold tolerance of plants [ 25 , 26 ], but BrCMF15 lacks MeJA-response elements. This is consistent with the high expression of the other genes according to the qPCR analysis.…”
Section: Resultsmentioning
confidence: 99%
“…promote reactive oxygen species (ROS) scavenging and contribute to the positive feedbac regulation of melatonin (MT) to enhance the cold tolerance of plants [25,26], but BrCMF1 lacks MeJA-response elements. This is consistent with the high expression of the othe genes according to the qPCR analysis.…”
Section: Transcriptome Analysis Of Brcmfsmentioning
confidence: 99%
“…These candidate genes encoded receptor-like protein kinases (RLKs), tRNA ligase, MYB transcription factor, BAX inhibitor motif-containing protein (BI1) -like protein, Chaperone DnaJ-domain superfamily protein (DnaJ), serine/threonine-protein kinase, and some uncharacterized proteins. Importantly, homologs of some candidate genes have been shown to be involved in cold tolerance ( Shakiba et al., 2017 ; Davik et al., 2021 ; Han et al., 2022 ; Li et al., 2022 ). Then, we examined the expression levels of RLK , MYB and DnaJ in two parents, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the region also contained a serine/threonine protein kinase, the homolog of which is LRK10L1.2 , reported to be a good candidate for regulating the effects of freezing tolerance at the QTL identified in Fragaria vesca L. ( Davik et al., 2021 ). MYB transcription factors are associated with the mechanism of cold tolerance in other plants ( Shakiba et al., 2017 ; Han et al., 2022 ; Li et al., 2022 ). Reportedly, DnaJ co-chaperons also play a vital role in stress response and have been found to be involved in the maintenance of PSII under chilling stress and the enhancement of drought tolerance in tomato ( Kong et al., 2014 ; Wang et al., 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Exogenous application of ABA not only induces CsCOR1 expression but also rapidly close stomata to reduce water loss, thereby ABA effectively alleviates chilling damage to plant, consistent with the changes in proline content ( Li et al., 2010a ; Hong et al., 2017 ). As efficient elicitor, exogenous methyl jasmonate application induces the expression of CsMYBs , and thus effectively promotes ROS scavenging and anthocyanin biosynthesis to alleviate cold stress damage ( Han et al., 2022 ). Melatonin treatment alleviates cold stress on tea plant by improving biosynthesis antioxidant enzyme and antioxidant defense and redox homeostasis ( Li et al., 2018a ; Li et al., 2018b ; Li et al., 2019a ).…”
Section: Regulatory Mechanisms Of Cold Tolerance Of Tea Plantsmentioning
confidence: 99%